POTENTIALS OF SYMPTOMATIC TREATMENT OF ACUTE RESPIRATORY TRACT INFECTIONS IN CHILDREN - L. R. Selimzyanova; E. A. Promyslova; E. А. Vishneva (Вопросы современной педиатрии, 2013)
Acute infection of upper respiratory tract is one of the most topical medical and social problems: it is respiratory diseases that cause the majority of children’s and adults’ non-attendance of school lessons and working days. Childhood respiratory infections are characterized by prolonged clinical course. The most common causes of upper respiratory tract infections are viruses, such as rhinovirus, respiratory syncytial virus, influenza and parainfluenza viruses, adeno-, corona- and metapneumoviruses as well as Coxsackie virus and ECHO virus. Antiviral agents are efficient only when administered during first 24–48 hours from the onset of disease, and a number of such drugs have only specific activity, therefore the limitation of possibilities of etiotropic therapy of acute respiratory infections can be established. This often leads to excessive inappropriate usage of antibacterial drugs. Such symptoms as nasal stuffiness and cough which accompany acute respiratory tract infections, can significantly affect patients’ and his family’s quality of life. Symptomatic therapy is traditionally used in order to relieve these symptoms. The article contains data on potentials of one of such symptomatic drugs in treatment of upper respiratory tract infections.